PERANCANGAN MANUAL SYSTEM REGISTER SENSUS PENDUDUK MENJADI BERBASIS VISUAL BASIC DI KECAMATAN CIAMPEL - SISKA AJSAHRI; Ahmad Anas; Kuni Hidayatal Masruroh (INFOKOM (Informatika & Komputer), 2022)
Good population management is needed to be able to provide services to related parties and to produce better performance. Accuracy and speed of presentation of data and information is one of the important factor in managing good population service. Therefore, we need a software that is able to handle the management of population services properly. Districts Ciampel is one of districts which a in regency Karawang, province West Java. Service research in the sub district which is engaged in serve the community still using manual system as report data register bookkeeping. Starting from plot very long queue, takes a very long time, lots of stacked files, could accur file easy to tear and damage. On the basis of the problem writer aims for designing register system population census manual replaced using Visual Basic from this research produce more modern system can be used by officer districts so that clearly with data more precise and accurate. This system can also help reduce long queues, then save time, prevent damage book/file and make it easy officer districts in the process registration register as a means serve the community.